Young Lives school survey 2016-17: Evidence from India - Moore, R; Azubuike, O; Reddy, P; Rolleston, C; Singh, R (Young Lives, 2017)
This country report provides an overview of the Young Lives secondary school effectiveness study conducted in India (Andhra Pradesh and Telangana) in 2016-17 with around 9,000 children in Class 9. The survey was designed to allow analysis of what shapes children's learning and progression over a school year, and this paper gives a descriptive report of some of the main areas of data. This secondary school study examined school effectiveness through three outcome measures: Class 9 students’ performance in maths; functional English; and transferable skills. Student performance in maths and functional English was assessed using repeated measures, with linked cognitive tests administered at the beginning and end of Class 9; this allowed students’ progress over the course of one year of secondary schooling to be considered in relation to their background, individual, class, teacher and school factors. This survey design has generated rich evidence about school and class effectiveness, and the drivers of learning within schools that children within the 20 Young Lives sites in Andhra Pradesh and Telangana could access.